Heterogeneity of the Conserved Ribosomal Ribonucleic Acid Sequences of Bacillus subtilis - Doi, Roy H. (1966)
Doi, Roy H. (University of California, Davis), and Richard T. Igarashi. Heterogeneity of the conserved ribosomal ribonucleic acid sequences of Bacillus subtilis. J. Bacteriol. 92:88–96. 1966.—Hybrid formation was demonstrated between Bacillus subtilis ribosomal ribonucleic acid (RNA) and deoxyribonucleic acid (DNA) from various bacterial species. The high degree of complementarity between B. subtilis ribosomal RNA and the DNA from B. cereus and B. stearothermophilus suggested a method to test whether the same RNA sequences were hybridizing with the DNA from these two species. Saturation studies with 16S and 23S RNA preparations from B. subtilis showed that a definite number of complementary sites was present in each DNA. Base composition analyses of the RNA in the hybrid demonstrated that ribosomal RNA sequences were involved. Hybrid competition studies revealed that B. stearothermophilus ribosomal RNA could compete totally against B. subtilis ribosomal RNA for B. stearothermophilus DNA, although it could compete only partially against the B. subtilis ribosomal RNA hybridizing with B. cereus DNA. These observations were made independently with both 16S and 23S ribosomal RNA preparations. These results revealed that different nucleotide sequences of B. subtilis ribosomal RNA were hybridizing with the DNA from B. cereus and B. stearothermophilus. Two possible interpretations of these results are: (i) different nucleotide sequences from a homogeneous ribosomal RNA population are hybridizing with heterologous DNA preparations, and (ii) ribosomal RNA cistrons are heterogeneous.